Insulative wood materials templated by wet foams. Issue 2 (20th December 2022) - Ferreira, Elisa S.; Dobrzanski, Elizabeth; Tiwary, Praphulla; Agrawal, Prashant; Chen, Richard; Cranston, Emily D.
Abstract : Insulative materials from forest residues prepared by oven-drying. Abstract : Insulative materials are lightweight structures that prevent heat transfer. Plastic foams and vitreous wools are the main materials currently used for insulation in construction, although their use is associated with environmental and health concerns. In this work, lightweight solid foams (0.12 g cm −3 ) with low thermal conductivity (0.042 W m −1 K −1 ) were produced from forest residue by a green and easily scalable route. In the preparation, unrefined pine beetle-killed wood was milled and assembled as expanded structures using highly stable aqueous wet foams. The wet stability was provided by poly(vinyl alcohol) (PVA) and sodium dodecyl sulphate, which reinforced the aqueous structure and enabled the foams to be dried without significant collapse. Additionally, PVA enhanced the compressive strength and mesopore volume of the wood foams, showing that mechanical and thermal properties of wood-based insulative materials could be improved by water-soluble polymers. The structural integrity of fibre foams was mantained after exposure to high humity, while the thermal conductivity increased with the moisture content of the materials. The materials could be fully reconstituted into foams by re-dispersing and re-foaming the components in water, which produced foams with the original density and performance. The combination of low thermal conductivity and high compressive strength indicated that wood foams can replace some of the commercially available insulation used in construction. Finally, this route to produce bio-based expanded structures from aqueous foams opens new opportunities for the development of more sustainable cellular materials without extensive mechanical/chemical refining of fibres.